The 'Moretum', the slavery and the Principate - Joly, Fábio Duarte (Romanitas - Revista de Estudos Grecolatinos, 2014)
This article focuses on the Moretum, a poem contained in the Appendix Vergiliana. The studies devoted to this poem usually analyze its literary structure, trying to qualify its style and relations with the epic genre. My purpose is to analyze it as part of discussions about slavery in the Early Roman Empire, which took place in the context of tensions between emperor and aristocrats during the Principate.
Keywords: Moretum; Slavery; Principate